Núcleo de prática jurídica das faculdades de direito como instrumento de consolidação da dignidade da pessoa humana - Moreira, Cristiano José de Azevedo (2012)
The considerable increase of graduate courses in Brazil brought a new perspective to the student from the teaching of 2° grade, which is replaced by a range of options in an attempt to enter an institution of higher education. With the courses of Law was no different. There are hundreds of courses across the country trying to provide a study grounded in positivism, in the use of the law, being made thinking and being able to convince many that she, the law, and the only source of law. Right arm of the courses of Legal Science (and often their showcase), the core of legal practice and the instrument of real guarantee of defense of the rights to a portion of the population lacks of socio-economic conditions to be a professional lawyer able to satisfy their longing for citizen, or at least, ease the anguish of their problems. In fact, the work done by students and teachers is of paramount importance in the learning, on the one hand, and for the formation of citizenship, of another. And this work is carried out by a Law School located outside of a capital and its metropolitan region, considerably increases its indispensability in the womb of an organized society. Inside, unlike the capital, the prevailing misinformation, combined with the lack of study, opportunities and understanding of the law, making care for assisted a real lecture on rights and citizenship, always seeking an accessible language, devoid of legal words, the "legalese" as a way of better absorption by the one who deserves a minimum of human dignity, as provided for in our Magna Carta. This study intends to address the topic of teacher-lawyer in his work in teaching and assisting the population together with their students and the satisfaction (or not) to be able to have the conscience of the resolution of "human problems" of the population served.